Kuasa Kepala Desa Atas Dana Desa di Desa Sodong Kabupaten Pandeglang - Novryan, Rama Adhi; Ilmar, Anwar (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Village Funds play a crucial role in improving the welfare of local communities. Ideally, the implementation of Village Funds should aim to create strong, advanced, independent, and democratic villages so that a village's potential can be utilized and empowered effectively and optimally. The government allocates Village Funds from the State Budget to finance villages in governance, development, community development, and empowerment of local communities. The study aims to explain and analyze the modus operandi of the Village Head in managing Village Funds. The research adopts a qualitative explanatory approach to explore specific phenomena in their context and gain deeper understanding by applying Antonio Gramsci's theoretical framework of hegemony. This theory is applied to analyze power dynamics, societal consensus, and patterns of corruption in Sodong Village. Initial findings indicate that the Sodong Village Head's modus operandi includes submitting fictitious activities and projects in Village Fund budget proposals. It was found that most of the projects and activities were implemented by the Finance Section Head, acting under the authority delegated by the Village Head, as well as by the Village Head himself. Structurally, the findings suggest a close personal relationship between the Village Head and several village officials, particularly those directly involved in managing Village Funds. The study concludes that the primary cause of corruption is the lack of transparency involving other village officials and project officers. This lack of transparency allows the Village Head to monopolize decision-making and implementation processes, leading to accountability failures and instances of corruption. Therefore, continuous efforts are needed to prevent corruption, such as regular monitoring of budget realization, strict oversight during fund disbursement, and annual evaluations of Village Fund implementation, particularly in villages across Pandeglang Regency.